2011
DOI: 10.1172/jci42520
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis surfactant peptides promote biofilm maturation and dissemination of biofilm-associated infection in mice

Abstract: Biofilms are surface-attached agglomerations of microorganisms embedded in an extracellular matrix. Biofilm-associated infections are difficult to eradicate and represent a significant reservoir for disseminating and recurring serious infections. Infections involving biofilms frequently develop on indwelling medical devices in hospitalized patients, and Staphylococcus epidermidis is the leading cause of infection in this setting. However, the molecular determinants of biofilm dissemination are unknown. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
304
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(318 citation statements)
references
References 43 publications
10
304
0
4
Order By: Relevance
“…Consistently, a strain lacking psm␣ had a decreased ability to cause skin lesions in mice and rabbits (9,23). In addition to this, Wang et al (24) have shown that the mortality rates and the levels of the inflammatory cytokine tumor necrosis factor alpha in the blood of mice infected with psm␣ or psm␥ mutant strains were substantially reduced. The PSM␤ peptides appear less important for cytolysis and inflammation but, in low concentrations, they seem to promote biofilm formation by Staphylococcus epidermidis.…”
Section: S Taphylococcus Aureus Is An Opportunistic Human Pathogen Thatmentioning
confidence: 79%
See 1 more Smart Citation
“…Consistently, a strain lacking psm␣ had a decreased ability to cause skin lesions in mice and rabbits (9,23). In addition to this, Wang et al (24) have shown that the mortality rates and the levels of the inflammatory cytokine tumor necrosis factor alpha in the blood of mice infected with psm␣ or psm␥ mutant strains were substantially reduced. The PSM␤ peptides appear less important for cytolysis and inflammation but, in low concentrations, they seem to promote biofilm formation by Staphylococcus epidermidis.…”
Section: S Taphylococcus Aureus Is An Opportunistic Human Pathogen Thatmentioning
confidence: 79%
“…The PSM␤ peptides appear less important for cytolysis and inflammation but, in low concentrations, they seem to promote biofilm formation by Staphylococcus epidermidis. High amounts of the same PSM␤ peptides do, however, promote the detachment of staphylococcal cells from biofilms both in vitro and in vivo (24).…”
Section: S Taphylococcus Aureus Is An Opportunistic Human Pathogen Thatmentioning
confidence: 99%
“…PSMa peptides have a cytolytic effect on neutrophils and monocytes that is not seen with other PSMs [17], so increased PSMa1 production may protect the bacteria from immune attack during the initial colonization phase of endocarditis. PSMs are also associated with both biofilm stabilization and detachment, depending on their concentration [26,27], and endocarditis is associated with S. aureus biofilms [28,29]. In contrast to studies on VISA isolates [13], there was no reduction in virulence in the G. mellonella model indicating that although agr activity was reduced and there were changes in PSM production, this was not associated with reduced acute virulence.…”
Section: Resultsmentioning
confidence: 97%
“…It was reported that S. epidermidis PSMs upregulate the neutrophil complement receptor CD11b via stimulation of the neutrophil formyl peptide receptor 2 (FPR2/ALX) in an agr-dependent manner, underlining the important role of FPR2/ALX and PSMs in bacteria-host interactions (Kretschmer et al, 2012). Six types of PSMs have been described thus far in S. epidermidis (Wang et al, 2011). PSMd represents the first potent cytolysin identified in this bacterial species (Otto, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that Hld cooperates with host-derived antimicrobial peptides in the innate immune system to reduce the survival of pathogenic group A streptococci (Cogen et al, 2010). Recently, it was demonstrated that PSMs are involved in S. epidermidis biofilm structuring and detachment in vitro as well as in vivo in a mouse model of device-related infection (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%